Strategi Komunikasi Siswa Dan Guru Kelas XI SMAN 2 Sangatta Utara Dalam Proses Pembelajaran Bahasa Indonesia - Syawal Arifin; Masrur Yahya; Mohammad Siddik (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2019)
The mastery of various foreign languages causes frequent obstacles in the delivery of messages to the speech partners. As a result, teachers and class XI students of SMAN 2 Sangatta Utara used various communication strategies to deal with these obstacles. This study aims to describe the communication strategies used by teachers and class XI students of SMAN 2 Sangatta Utara in the class of Indonesian Language lessons. This research was done by a descriptive method and qualitative approach. The data was collected in March to October 2017 from one classroom teacher and one class XI of grade student of SMAN 2 Sangatta Utara. Data retrieval was carried out during the teaching and learning activities in the classroom when the teacher is teaching the Indonesian language. This study uses skillful free listening techniques to collect data. The data analysis was used the flow technique, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions. The validity test of the data is done by (1) persistence observations, (2) peer examination, and (3) triangulation. The results study included: (1) when communicating with classmates, students use various communication strategies namely imitation communication strategies, the use of certain body language according to the meaning of communication that they want to achieve, and the transfer awareness communication strategies. (2) communication strategies in the classroom are mostly carried out by the teacher when communicating with students. The communication strategy of students with teachers includes (a) paraphrase, (b) transfer awareness type, (c) asking for help type, (d) avoiding type and (e) imitating type.